Efek Posisi Lateral Terhadap Hemodinamik Pasien yang Terpasang Ventilasi Mekanik: Literature Review . - yuswandi; ismafiaty; musri (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
ABSTRACT Title: Effects of Lateral Position on Hemodynamics in Patients Attached to Mechanical Ventilation: Literature Review Background: One of the nursing interventions in the management of patients with mechanical ventilation is a change in position. Several studies have shown there are hemodynamic changes in the lateral position. The right lateral position can increase vagal activity and decrease sympathetic activity in patients with heart failure while other studies suggest that the left lateral position can improve ventilation, this is because the anatomy of the heart is in the left position between the top and bottom of the lungs so that it creates pressure. the lungs are increased and the pressure at the apex is lower than at the basal part of the lungs, so it is necessary to do further investigation regarding the lateral position of the hemodynamics Method: This study aimed to determine the effect of lateral position on the hemodynamic status of mechanically ventilated patients. The research design used was a literature review design. The population in this study were journals related to lateral position and hemodynamic status attached to mechanical ventilation, obtained from reputable journals with national and international standards.ResultIt : There are 6 journals from 8 journals stating that there is an effect of lateral position on the hemodynamics of patients who are attached to mechanical ventilation which includes blood pressure, heart rate, respiratory rate but does not affect oxygen saturation..Conclusion : Lateral positions (left and right) can increase blood pressure and MAP, increase and decrease heart rate, increase respiratory rate but have no significant effect on oxygen saturation..